Wife on his doorstep [large type] - Johns, Patricia (Romance writer) (Johns, Patricia. Redemption's Amish Legacies., 2021)
"When Miriam Lapp arrives unannounced at her estranged husband's house, she has no intention of staying. But she can't walk away when Amos's ailing grandmother needs a woman's support. She'll help temporarily, then leave to start her own Amish business. But spending time together makes Miriam and Amos question their past mistakes. Can a once mismatched couple find love ten years later?"--